Deep learning based monocular visual-inertial odometry - Mahdi Abolfazli Esfahani (Nanyang Technological University, 2021)
Autonomous vehicles require knowing their state in the environment to make a decision and achieve their desired goal. The Visual-Inertial Odometry (VIO) system is one of the most significant modules of autonomous vehicles. This module enables robots to know their position and orientation, relative to the starting point, in the environment. Despite decades of research using different sensors, current odometry systems suffer from various kinds of problems, resulting in odometry failure.